1989
DOI: 10.1177/089686088900900113
|View full text |Cite
|
Sign up to set email alerts
|

Tenckhoff Catheter Replacement or Intraperitoneal Urokinase: A Randomised Trial in the Management of Recurrent Continuous Ambulatory Peritoneal Dialysis (CAPD) Peritonitis

Abstract: A randomised trial, comparing Tenckhoff catheter replacement as a one-stage procedure and i.p. urokinase, was undertaken in the management of recurrent continuous ambulatory peritoneal dialysis (CAPD) peritonitis. In addition to appropriate i.p. antibiotic treatment, 17 patients received i.p. urokinase (5000 i.u.) on the second and fourth days of antibiotic treatment, and 14 patients underwent CAPD catheter replacement. An additional six patients also underwent catheter replacement following the recurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 5 publications
0
26
0
1
Order By: Relevance
“…The rates of complete cure, catheter removal, or relapsing episode, as well as overall mortality were not affected by adjunctive treatment with IP urokinase. In contrast, 1 randomized controlled study showed that simultaneous catheter removal and replacement was superior to IP urokinase in reducing relapsing peritonitis episodes ( 341 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…The rates of complete cure, catheter removal, or relapsing episode, as well as overall mortality were not affected by adjunctive treatment with IP urokinase. In contrast, 1 randomized controlled study showed that simultaneous catheter removal and replacement was superior to IP urokinase in reducing relapsing peritonitis episodes ( 341 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…Williams et al, however, found that replacement of the catheter instead of urokinase therapy led to fewer repeat episodes. 40 Decreased macrophage bactericidal activity, opsonic activity, and immunoglobulin G concentration of peritoneal effluent have been found in children with a high rate of peritonitis.…”
Section: Relapsing Peritonitismentioning
confidence: 99%
“…Williams et al . performed a randomised controlled trial in which 17 patients received intraperitoneal urokinase (5000 IU) on the second and fourth days of appropriate antibiotic treatment for CAPD peritonitis; 14 patients underwent catheter replacement 1 . A further 6 patients who had a recurrence of peritonitis after urokinase treatment underwent catheter replacement.…”
Section: What Is the Evidence?mentioning
confidence: 99%